Path Analysis of Customer Reviews, Brand Image, to Consumer Trust and Loyalty in the Online Marketplace in Binjai - Sugianto, Sugianto; Marliyah, Marliyah; Nasution, Junita Muharani (Budapest International Research and Critics University, 2021)
Based on data from Iprice.co.id that in Indonesia there are 5 marketplaces with the most visitors namely, Shoppe, Tokopedia, Lazada, Bukalapak, and Blibli with 11.9% of the total population of Indonesia users. The change in buying and selling transactions from traditional to digital causes consumer trust and loyalty to become something important to be instilled and maintained, consumer trust and loyalty are influenced by several factors, namely customer reviews and brand image. Customer reviews affect consumer confidence to decide on a purchase, a good brand image will increase consumer trust and create loyalty. This study uses a field approach by distributing online questionnaires as many as 160 samples. The data analysis technique used is path analysis technique with SPSS version 16. The results show that there is no direct influence of customer reviews and brand image variables on consumer trust in the online marketplace in Binjai with partial testing and has a significant effect with simultaneous testing, while on the variable of consumer loyalty there is a direct influence of the variables of customer reviews and consumer trust either partially or simultaneously testing.